2020
DOI: 10.1038/s41467-020-15196-x
|View full text |Cite
|
Sign up to set email alerts
|

Polaritonic molecular clock for all-optical ultrafast imaging of wavepacket dynamics without probe pulses

Abstract: Conventional approaches to probing ultrafast molecular dynamics rely on the use of synchronized laser pulses with a well-defined time delay. Typically, a pump pulse excites a wavepacket in the molecule. A subsequent probe pulse can then dissociates or ionizes the molecule, and measurement of the molecular fragments provides information about where the wavepacket was for each time delay. In this work, we propose to exploit the ultrafast nuclear-position-dependent emission obtained due to large light-matter coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 60 publications
4
58
0
Order By: Relevance
“…We observe that the avoided crossings are located at the edges of the oscillation coordinate q osc , where the WP velocity approaches zero as it reverts its motion. Coherently with the study by Silva et al, 60 we then see that a more efficient transfer to | S 0 , 1⟩ is obtained when the WP moves slowly and spends more time in the coupled region; that is, its motion tends to follow the adiabatic behavior introduced above. The pseudoharmonic oscillation around the S 2 min is also responsible for the stair-like population dynamics of the | S 2 , 0⟩ state, presented in Figure 2 c. In particular, the transfer occurs only when the WP hits the resonant region sitting at the limit of q osc .…”
supporting
confidence: 85%
“…We observe that the avoided crossings are located at the edges of the oscillation coordinate q osc , where the WP velocity approaches zero as it reverts its motion. Coherently with the study by Silva et al, 60 we then see that a more efficient transfer to | S 0 , 1⟩ is obtained when the WP moves slowly and spends more time in the coupled region; that is, its motion tends to follow the adiabatic behavior introduced above. The pseudoharmonic oscillation around the S 2 min is also responsible for the stair-like population dynamics of the | S 2 , 0⟩ state, presented in Figure 2 c. In particular, the transfer occurs only when the WP hits the resonant region sitting at the limit of q osc .…”
supporting
confidence: 85%
“…Although, in both studied situations, emission occurs quite obviously whenever the nuclear wavepacket is found at a geometry resonant with the cavity, in Ref. 36 no SR enhancement in the emission rate is observed. The reason for this is the fact that the laser pulse excites the system in the perturbative, one-photon regime, in which SR cannot take place.…”
Section: B Pyrazine Ensemble Coupled To the Cavity Via The S 0 -S 2 mentioning
confidence: 85%
“…Recently, it has been shown theoretically that the time-dependent emission of a low-Q cavity can be used to track the intramolecular dynamics after excitation of the ensemble. 36 It was demonstrated that the motion of the nuclear density in and out of the resonance region can be followed through the emission characteristics, as an emission requires the population of polaritonic modes, which are local probes of the molecular configuration. Although, in both studied situations, emission occurs quite obviously whenever the nuclear wavepacket is found at a geometry resonant with the cavity, in Ref.…”
Section: B Pyrazine Ensemble Coupled To the Cavity Via The S 0 -S 2 mentioning
confidence: 99%
“…This is because, soon after its generation, the exciton vibrational wavepacket remains in the vicinity of the Franck–Condon region before exploring the potential energy surface of the excited state. 61 Hence, within a very short time scale, vibrations do not play any role yet and the TLS model describes the molecular decay. This time scale, τ 1 , can be estimated as a fraction of the period associated with the RC harmonic motion, T RC = 2π/ω RC .…”
Section: Resultsmentioning
confidence: 99%